If `y= sum_(n=0)^(oo)a_nx^n` is solution to the equation `(x^2+1)y'' + 6xy' + 6y =0`

`y'=sum_(n=1)^(oo)na_nx^(n-1)`

`y''=sum_(n=2)^(oo)(n(n-1)a_nx^(n-2)`

`(1+x^2)y''=sum_(n=2)^(oo)n(n-1)a_nx^(n-2)+sum_(n=2)^(oo)n(n-1)a_nx^(n-2)x^2`

`(1+x^2)y''=sum_(n=2)^(oo)n(n-1)a_nx^(n-2)+sum_(n=2)^(oo)n(n-1)a_nx^n`

`xy'=sum_(n=1)^(oo)na_nx^(n-1)x=sum_(n=1)^(oo)na_nx^(n)`

If we plug it in the differential equation,

`sum_(n=2)^(oo)n(n-1)a_nx^(n-2)+sum_(n=2)^(oo)n(n-1)a_nx^n+6sum_(n=1)^(oo)na_nx^(n)+ 6sum_(n=0)^(oo)a_nx^n=0`

In the first sum, make the...

(The entire section contains 353 words.)

## Unlock This Answer Now

Start your **48-hour free trial** to unlock this answer and thousands more. Enjoy eNotes ad-free and cancel anytime.

Already a member? Log in here.